POLA DAN ARAH MIGRASI PENDUDUK ANTAR PROPINSI DI INDONESIA TAHUN 1990 - Ida Bagoes Mantra (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1992)
Inter provincial migration in Indonesia has long been known. The 1990 Population Census of Indonesia reveals that throughout the provincies of Indonesia the birth place of most of the inhabitants was not the province where they now live. The number of these migrants kept increasing, and had reached 14.8 million by the year 1990.The size of the flow of migrants to a certainprovince is very much influenced by the upsand downs of the development of the province since their reasons to migrate are mostly due to economic matters. Since most of the development of Indonesia has been intensified in the northern and eastern parts of the country, it has been observed that since 1990 there has been an increasing flow of migrants heading to these areas.On the whole, migrants preferred to go to the cities rather than to the rural areas. Nevertheless, in the provinces out side Jawa and Bali most people preferred to migrate to the rural areas.